Vector saliva in vaccines for visceral leishmaniasis: A brief encounter of high consequence? - Shaden eKamhawi; Hamide eAslan; Jesus G Valenzuela (Frontiers Media S.A., 2014)
Visceral leishmaniasis (VL) is a vector-borne disease transmitted by phlebotomine sand flies and remains the most serious form of the disease with no available human vaccine. Repeatedly, studies have demonstrated the immunogenicity and protective efficacy of a number of sand fly salivary proteins against cutaneous and visceral leishmaniases. All Leishmania species including agents of VL are co-deposited into the skin together with vector saliva. Generally, the immune response to a protective salivary protein in vaccinated animals is rapid and possibly acts on the parasites soon after delivery into the skin by the bite of an infective sand fly. This is followed by the development of a stronger Leishmania-specific immunity in saliva-vaccinated animals compared to controls. Considering that several of the most efficacious protective molecules were identified from a proven vector of VL, we put forward the notion that a combination vaccine that includes a Leishmania antigen and a vector salivary molecule has the potential to improve vaccine efficacy by targeting the parasite at it most vulnerable stage just after transmission.